Assessing the impact of urban morphology on community resilience in sustainable urban development: A case study of the historic urban fabric of Kerman - Mohammad Dabdabeh; Yashar Gharachamani Asl; Amir Hossein Farahinia (آلودگی‌های محیطی و توسعه پایدار شهری)
The physical expansion of a city, when not properly aligned with its natural and historical structures, can lead to failures in urban development processes, particularly in cities with distinctive natural features. Kerman, one of Iran's historical cities with a unique cultural identity, has not been immune to the damages caused by industrial and modern development. Physical and social vulnerabilities, such as urban expansion driven by capitalist and land-centric perspectives, the spread of new lifestyles with distinct values, neglect of natural structures and historical fabric as sustainable models, car-centric urban design, and scattered migration and growth, have propelled Kerman toward extensive challenges. This study specifically examines and evaluates community resilience through quantitative research, exploring how urban morphology influences the reduction of vulnerability in historical cities from the residents' perspective. The main research question is: How can urban morphological factors be classified to increase community resilience in the historical urban fabric of Kerman? To assess the research hypotheses, field data were collected through explanatory and dispersed survey strategies, utilizing 388 questionnaires. Data analysis was conducted using Exploratory Factor Analysis (EFA) to group factors. The findings indicate that the classification of urban morphological options in Kerman's historical fabric can be divided into three categories: "Constant Factors in the Current Situation," "Challenging Factors," and "Indifferent Factors." The challenging factors include healthcare facility axes (loading factor 0.932), vehicular access (loading factor 0.926), pedestrian access (loading factor 0.664), density of populous land uses (loading factor 0.905), building quality (loading factor 0.866), abandoned and dilapidated buildings (loading factor 0.781), and public space axes (loading factor 0.729). This study demonstrates that planning, principled management, and attention to sustainable patterns within the city's historical and natural fabric are key to reducing vulnerability and increasing urban resilience for effective urban development.